Classification of traveling wave solutions for time-fractional fifth-order KdV-like equation - İnç, Mustafa; Kilic, Bulent (Taylor & Francis Ltd, 2014)
In this paper, we studied time-fractional nonlinear partial differential equations to reach their some solutions. There are lots of explicit and analytic methods in the literature. We used Kudryashov, Exp-function, and Jacobi elliptic rational expansion methods. By using these methods, we get some solutions of time-fractional fifth-order KdV-like equation.
Keywords: Elliptic Function Expansion; Exp-Function Method; 1St Integral Method; Periodic-Solutions